Selenium and its relationship to cancer: an update - Whanger, P. D. (British journal of nutrition, 2004)
Selenomethionine (Semet) is the major seleno-compound in cereal grains and enriched yeast whereas Se-methylselenocysteine (SeMCYS) is the major seleno-compound in Se-accumulator plants and some plants of economic importance such as garlic and broccoli exposed to excess Se. Animals can metabolize both Semet and SeMCYS. Epidemiological studies have indicated an inverse relationship between Se intake and the incidence of certain cancers. Blood or plasma levels of Se are usually lower in patients with cancer than those without this disorder, but inconsistent results have been found with toenail-Se values and the incidence of cancer. There have been eight trials with human subjects conducted on the influence of Se on cancer incidence or biomarkers, and except for one, all have shown a positive benefit of Se on cancer reduction or biomarkers of this disorder. This is consistent with about 100 small-animal studies where Se has been shown to reduce the incidence of tumours in most of these trials. Se-enriched yeast is the major form of Se used in trials with human subjects. In the mammary-tumour model, SeMCYS has been shown to be the most effective seleno-compound identified so far in reduction of tumours. Several mechanisms have been proposed on the mechanism whereby Se reduces tumours. Even though SeMCYS was shown to be the most effective seleno-compound in the reduction of mammary tumours, it may not be the most effective seleno-compound for reduction of colon tumours.